Can historical economic growth patterns be traced in South and Southeast Asian countries as the classical theory suggests? - Muhammad Tashfiq Huq; Masaru Ichihashi (Journal of Economic Structures)
Abstract According to the classical theory of economic development, as in Akamatsu’s flying geese model, many countries should exhibit similar development patterns from agriculture-based sectors to processed or labor-intensive industries as a long-run trend. This paper identifies some common development patterns in 6 Asian lower-income developing countries (LIDCs) to confirm Flying Geese model for South and Southeast Asia, using three periods of the input‒output table with a novel decomposition technique derived from a conventional method. Our results show that labor-intensive and light manufacturing sectors, along with some high-value-added service sectors, are the most promising sectors in these countries. Food, basic metal and textiles in manufacturing and construction, electricity and transport in service are commonly growing in most countries. Among our targeted Asian countries, only Vietnam has been developing many diversified sectors in manufacturing from traditional labor-intensive sectors to highly technology-oriented sectors. This means that Vietnam might achieve an advanced stage faster than other Asian countries. In addition, we have found some prospective accelerating sectors in these countries with our novel decomposition technique, such as manufacturing and recycling, basic metal, and rubber. These findings indicate that these countries have started to diversify industries from their traditional sectors, which resembles the flying geese model.